Custom‐built constrained uniaxial and rotating hinge total knee replacement in cats: Clinical application, design principles, surgical technique, and clinical outcome. Issue 6 (5th July 2021) - Fitzpatrick, Noel; Miraldo, Diogo C.; Meswania, Jay
Abstract: Objective: To describe the design principles and evolution, surgical technique, and outcome for custom constrained (uniaxial and rotating hinge) total knee replacement (TKR) in cats. Study design: Retrospective case series. Animals: Nine cats with traumatic stifle luxation (n = 8) or severe distal femoral deformity (n = 1) were considered suitable candidates. Methods: Cats that met eligibility criteria and received a custom TKR between 2009 and 2018 by a single surgeon were included in this case series. Three generations of implant were used. Implant positioning was assessed by postoperative orthogonal radiography. Functional outcome was determined by clinical assessment, owner interview, and a feline musculoskeletal pain index questionnaire. Results: Median clinical follow‐up time was 12 months (range, 4‐41); follow‐up time was increased to 29 months (range, 22‐47) when results of functional questionnaires with owner were included. Median radiographic follow‐up was 12 months (range, 4‐25). One cat had a catastrophic outcome. Three cats had good outcomes, and five cats had excellent outcomes. Conclusion: Most cats treated with custom‐built TKR achieved good to excellent outcomes. Clinical significance: Custom TKR is a viable option for the treatment of severe pathologies of the feline stifle. Additional research is required to fully evaluate implant suitability.